Coupling Hematoma Evacuation with Immune Profiling for Analysis of Neuroinflammation After Primary Intracerebral Hemorrhage: A Pilot Study - Lusk, Jay B.; Quinones, Quintin J.; Staats, Janet S.; Weinhold, Kent J.; Grossi, Peter M.; Nimjee, Shahid M.; Laskowitz, Daniel T.; James, Michael L. (World neurosurgery, 2022)
We sought to explore the use and feasibility of an integrated hematoma evacuation/tissue preservation system coupled with immune profiling to assess human ex vivo immune cell populations from brain hematoma samples after intracerebral hemorrhage (ICH). In this nonrandomized, noncontrolled pilot/feasibility study of 7 patients with primary supratentorial ICH, a hematoma evacuation device and integrated tissue preservation system were used to obtain hematoma samples during surgical evacuation. Samples were processed, cryopreserved, and analyzed using flow cytometry to determine the relative distribution of immune cell populations compared with peripheral blood mononuclear cells from healthy control subjects. This study demonstrates proof of concept for an integrated hematoma evacuation and sample preservation system to collect human brain hematoma samples for flow cytometry analysis after acute human ICH. In our preliminary analysis, hematoma samples demonstrated a different makeup of white blood cells than peripheral blood from healthy controls. Flow cytometry analysis of hematoma samples in ICH demonstrates the potential to provide important insights into neuroinflammation associated with ICH.